2023
DOI: 10.1038/s41598-023-30828-0
|View full text |Cite
|
Sign up to set email alerts
|

Waste cooking oil processing over cobalt aluminate nanoparticles for liquid biofuel hydrocarbons production

Abstract: The catalytic conversion of waste cooking oil (WCO) was carried out over a synthetic nano catalyst of cobalt aluminate (CoAl2O4) to produce biofuel range fractions. A precipitation method was used to create a nanoparticle catalyst, which was then examined using field-emission scanning electron microscopy, X-ray diffraction, energy dispersive X-ray, nitrogen adsorption measurements, high-resolution transmission electron Microscopy (HRTEM), infrared spectroscopy, while a gas chromatography-mass spectrometer (GC–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 70 publications
0
1
0
Order By: Relevance
“…B20-B80 biodiesel blends showed lower emissions of the exhaust gas (except for the NO x level), while the hybrid fuel was characterized by a significant reduction in NO x level and comparable emissions of other exhaust gas (except unburned hydrocarbons) due to lower thermal efficiency compared with petrodiesel. Research results [38][39][40] have confirmed the feasibility of using mixtures of pongamia oil (MEOP), a 20% mixture of methyl ether of mahua oil (MEOM), and a 20% mixture of methyl ether of hybrid vegetable oil (MEHVO) with 80% pure diesel. However, a study of the influence of this fuel on technical and operational indicators has not been conducted.…”
Section: Introductionmentioning
confidence: 99%
“…B20-B80 biodiesel blends showed lower emissions of the exhaust gas (except for the NO x level), while the hybrid fuel was characterized by a significant reduction in NO x level and comparable emissions of other exhaust gas (except unburned hydrocarbons) due to lower thermal efficiency compared with petrodiesel. Research results [38][39][40] have confirmed the feasibility of using mixtures of pongamia oil (MEOP), a 20% mixture of methyl ether of mahua oil (MEOM), and a 20% mixture of methyl ether of hybrid vegetable oil (MEHVO) with 80% pure diesel. However, a study of the influence of this fuel on technical and operational indicators has not been conducted.…”
Section: Introductionmentioning
confidence: 99%